Technological and sustainable strategies for reducing losses and maintaining the quality of soybean grains in real production scale storage units. (May 2020) - Coradi, Paulo Carteri; de Oliveira, Marília Boff; de Oliveira Carneiro, Letícia; Coelho de Souza, Guilherme Abreu; Elias, Moacir Cardoso; Brackmann, Auri; Teodoro, Paulo Eduardo
Abstract: Soybean is the oilseed most cultivated worldwide and is in full production expansion in Brazil. However, the logistics and grain quality in post-harvest stages is increasingly concerning. The objective of this work was to evaluate different sustainable strategies of managing the mass of soybean grains in function of water content, optimizing the combined drying and storage operations to improve grain flow and quality in real production scale storage units. The experimental were consisted in two step, first: moisture soybean (SUL) (17%), dry soybean from the RR crop (SSLRR) (14%), dry soybean from the RR2 crop (SSLRR2) (14%), soybean dried in a continuous dryer (SSS1) (12%), in silo-dryer (SSS2) (14%), and in intermittent dryer (SSS3) (14%), moisture soybean (SUL) submitted to aeration drying (Silo 1), to partial drying (SSS1, SSS2, SSS3), and supplemented with aeration drying (Silo 2), dry soybean from the RR2 crop (SSLRR2) and stored in aeration (Silo 3), dry soybean from the RR crop (SSLRR) and stored in aeration (Silo 4), and second step: the lots of soybean (RR and RR2) was submitted the drying at low air temperatures of 35, 45, and 55 °C until the grains reached water content of 12% for cold storage at 10 and 20 °C, over two months. It was determined the physical and physical-chemical quality of soybean grains before and after drying and during the time in storage. The best option of preprocessing and storage strategy to obtain soybean flow and quality in high-capacity storage and handling unit was the combined drying (SSS1, SSS2, SSS3) and dry-aeration storage systems. The soybean grains harvested at high water contents submitted to drying at low temperatures and stored under artificially refrigerated conditions presented better grain quality over storage time but increased the operational drying time, hindering the flow of grain mass. Graphical abstract: Image 1 Highlights: Soybean harvested with high water content obtained quality after drying and storage. The drying and storage at low temperatures had the best quality results in the grains. The soybean batches submitted to continuous drying had better results of flow. The soybean submitted to partial drying and dry aeration obtained quality and flow.